مخطوط "تحلية الذهب في علم القضاء والأدب" لأبي عمران المازوني (831هـ) من اللوحة 03 إلى اللوحة 13 -دراسة وتحقيق - اليمان, سالم (University of Eloued-جامعة الوادي, 2022)
"ملخص البحث يَتعلّقُ هَذا البَحث بِفنِّ تَحقيقِ التُّراثِ؛ وهو إخرَاج كِتاب نوازل المازوني""تحلية الذّهب في علم القضاء والأدب"" إِلى النّورِ ومُحاوَلة تَوثيقِه كَمَا أرَادهُ الـمُؤَلِّف أو قَرِيباً مِنهُ. ونَستَهِلُّ هذا البَحث بِمقدِّمَة بِها أَهمّ الخُطُواتِ الـمـُتّبعَة، ثمّ يأتي قِسم دِراسي يَحتوي عَلى فَصلَين: الفَصل الأول: دِراسة حَياة المازوني أبي عمران موسى بن عيسى، وعصره، وأَمّا الفَصل الثَّاني: عَن كِتابه""تحلية الذّهب"" وأَهمِّيته ونِسبتُه إليه، وبَعد ذَلك نَشرعُ في قِسم التَّحقيقِ؛ وهُو تَفرِيغُ النّصِّ وِفقَ قَواعد الإملاء والكتابة الحديثة، وتَوثيق الأقوال والتَّعلِيق على ما يحتاج إلى تَعلِيق. وفي الأخِير جَعلتُ خَاتمة لأهَمِّ النَّتائِج، والتَّوصِيات، وأَهمُّهَا العِنايَة بِهذَا الفَنّ ونَفضِ الغُبارِ عَليهِ، وتحقيق كتب المازوني، وذَيّلتُ هَذا العَمل بِفهَارسَ عِلميةٍ لِكلِّ مَا يَحتويهِ البَحث.""Research Summary This research relates to the art of achieving heritage; It is directed by the book Nawazil mazzoni ""Sweetening Gold in Science judiciary and literature ""to light and try to document it as the author wanted or close to it. We start this research with an introduction with the most important steps followed, and then a study section wit Two chapters: Chapter I: Study the life of Mazoni Abiy Imran Musa Ben-Issa, and his erea and Chapter II: on, his book ""The Sweetening of Gold"" and its significance and attribution after which we proceed to the Investigation Section; It is to empty the text according to modern dictates and writing rules, document statements and comment on what needs to be commented upon. Finally, I made a conclusion to the most important findings, recommen- dations, the most important of which is to take care of this art and dust it, and to achieve the mazoni books and I appended this work with scientific indices for all its research. On it, the Mazoni books were investigated, and this work was appended with scientific indices that would have contained research."
مذكرة ماستر
Keywords: تحلية الذهب - نوازل المازوني - أبو عمران موسى; Sweetening Gold - Nawazil mazzoni- Abiy Imran Musa